Redes de redistribuição de sinais a partir de redes de freqüência única (SFN) - Novaes, Carolina Duca (2010)
This dissertation presents details of a structure needed to create a Single Frequency Network (SFN) using low-power transmitters, and a comparison with a network composed of a single transmitter with high power. Among the difficulties to implement networks which distribute signals in SFN, has prioritized the synchronization issue and equalization techniques to achieve better performance of this system. Thus, there was a theoretical research comparing the different methods of timing of single frequency networks and simulations of coverage and performance in order to discuss the implementation of such a network system in the Brazilian digital TV (SBTVD).